DEVELOPMENT OF THE METHOD FOR MONITORING AND STUDYING OF FRACTURE OF METALS IN VERY HIGH CYCLE FATIGUE REGIME - Prohorov, A.E.; Vshivkov, A.N.; Plekhov, O.A. (Perm Federal Research Centre Journal, 2015)
The paper deals with the development of hardware and software for monitoring of the internal defect structures under the material surface initiated during the fatigue test. The hardware is based on ferromagnetic detector. The detector is a modification of ferro-probes method. The fatigue test is conducted in a very high cycle fatigue regime with frequency 20 kHz. The obtained data allow us to conclude that the specimen fracture leads to the changes of magnetic properties of material. This makes it possible to predict crack propagation using the data obtained on the early stages of their evolution.